1991
DOI: 10.1056/nejm199111073251902
|View full text |Cite
|
Sign up to set email alerts
|

Second Neoplasms after Acute Lymphoblastic Leukemia in Childhood

Abstract: There is a substantial excess of second neoplasms, especially of the central nervous system, among children treated for ALL. Children five years old or younger and those receiving radiation are at higher risk, especially for second tumors arising in the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
261
1
14

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(287 citation statements)
references
References 30 publications
11
261
1
14
Order By: Relevance
“…In total 230 SMNs (0.99%) were reported among 23,051 children treated for ALL (Table I). This percentage (0.99%) is similar to the 1.18% and 2.5% cumulative risk of SMN at 10 years and 15 years, respectively, reported by Bhatia and Neglia [3,4]. The most common SMNs observed in this review were CNS tumors (31.7%) followed by AML/MDS (16.5%), thyroid cancer (10%), lymphomas (8.2%), and skin cancer (7.8%).…”
Section: Discussionsupporting
confidence: 83%
“…In total 230 SMNs (0.99%) were reported among 23,051 children treated for ALL (Table I). This percentage (0.99%) is similar to the 1.18% and 2.5% cumulative risk of SMN at 10 years and 15 years, respectively, reported by Bhatia and Neglia [3,4]. The most common SMNs observed in this review were CNS tumors (31.7%) followed by AML/MDS (16.5%), thyroid cancer (10%), lymphomas (8.2%), and skin cancer (7.8%).…”
Section: Discussionsupporting
confidence: 83%
“…A significant amount of information regarding second malignancies following treatment of Hodgkin disease, [1][2][3] retinoblastoma, 4 -6 and acute lymphoblastic leukemia (ALL) 7 is available because a good cure rate has been achieved for many years, resulting in many long-term survivors.…”
mentioning
confidence: 99%
“…22 Osteosarcoma following ALL, on the other hand, seems to be very rare. No osteosarcomas were detected in a population-based series of eight second malignant neoplasms in 895 childhood ALL patients, 23 none among 43 second neoplasms in 9720 children with ALL treated according to the therapeutic protocols of the Children's Cancer Study Group, 24 and only one of 52 second neoplasms among 5006 ALL patients observed by the BFM group until 1997 25 (corresponding to patient 1 from this report, Schrappe M, personal communication) was an osteosarcoma. Evidence suggestive of a familial cancer predisposition was present in two of our three ALL patients.…”
Section: Discussionmentioning
confidence: 65%